Fiscal and Monetary Policies Interactions in Nigeria and South Africa: Dynamic Stochastic General Equilibrium Approach - Sanusi, Kazeem Abimbola; Dickason-Koekemoer, Zandri (International Journal of Economics and Financial Issues, 2023)
The interaction between fiscal and monetary policies in achieving macroeconomic goals has been a subject of debate, particularly on whether they complement or substitute each other. This issue arises when both policy authorities are independent of each other. This study aims to revisit the interaction of fiscal and monetary policies in Nigeria and South Africa using a dynamic stochastic general equilibrium model (DSGE) and calibration technique. The model consists of 20 equations that illustrate the behaviour of endogenous variables. The parameters are obtained from relevant DSGE literature and economic intuitions about the two economies. The findings reveal that fiscal and monetary policy variables interact in both economies. Inflation responds to fiscal policy shocks such as government spending, revenue and borrowing shocks. Monetary authorities’ decisions such as interest rates and inflation also affect fiscal policy variables. However, the performance of monetary and fiscal policy variables is better in South Africa than in Nigeria. The study recommends closer coordination between the monetary and fiscal authorities in both economies to resolve policy design and implementation issues. Government monitoring and assessment units should also be strengthened to track the implementation and delivery of policies decided upon at coordination meetings.